2020
DOI: 10.3934/microbiol.2020025
|View full text |Cite
|
Sign up to set email alerts
|

Fecal carriage of ESBL-producing <em>Escherichia coli</em> in Egyptian patients admitted to the Medical Research Institute hospital, Alexandria University

Abstract: Commensal ESBL-producing E. coli represent a reservoir for resistance genes therefore, their detection is crucial to restrain the spread of beta-lactam resistance. Hence, the aim of the present study was phenotypic and genotypic characterization of commensal ESBL-producing E. coli obtained from the stool of patients at the time of admission and at the time of discharge from the Medical Research Institute hospital. A total of 70 E. coli isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The increased ratio of multidrug-resistant E. coli among ESBL positive isolates suggests that resistance to other antibiotic classes is being co-selected. Similarly, previous studies reported MDR organisms in faecal and sewage sludge samples ( 41 , 65 , 66 , 68 , 70 ). The most frequently used antibiotics in Bangladesh are cephalosporins and penicillins ( 92 ), which explains the reason for the isolates being resistant to cephalosporins and penicillins.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The increased ratio of multidrug-resistant E. coli among ESBL positive isolates suggests that resistance to other antibiotic classes is being co-selected. Similarly, previous studies reported MDR organisms in faecal and sewage sludge samples ( 41 , 65 , 66 , 68 , 70 ). The most frequently used antibiotics in Bangladesh are cephalosporins and penicillins ( 92 ), which explains the reason for the isolates being resistant to cephalosporins and penicillins.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, ESBL producing E. coli was recovered from 78% (42/54) of the inlet and 69% (37/54) of the outlet samples. Previously, ESBL producing E. coli were recovered from faecal samples ( 41 , 65 68 ) and sewage sludge ( 69 , 70 ). Recovery of ESBL E. coli from the samples manifested a real probability of bacterial circulation within the FSTPs and might also escape to the surrounding environment and eventually contaminate the surface water and groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of commensal E. coli from human fecal samples, ElBaradei et al found high abundances of ESBL carriers or even multidrug resistance. This is alarming, since these strains are associated with an increased risk of infection [ 42 ]. Similar E. coli clones belonging to the commensal phylogroup A were increasingly reported in association with ESBL production [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli is generally used as an indicator of antibiotic resistance because it can easily transfer antibiotic-resistance genes to other bacterial strains in the Enterobacteriaceae family, especially through plasmid mediation ( Radhouani et al ., 2012 ). Feces have been identified as a major reservoir of E. coli that harbor extended-spectrum beta-lactamase (ESBL) genes such as bla CTX-M , bla TEM , and bla SHV ( ElBaradei et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%